2018
DOI: 10.1628/093245615x14188909230136
|View full text |Cite
|
Sign up to set email alerts
|

Do Physicians Respond to Liability Standards?

Abstract: In this paper, we explore the sensitivity in the clinical decisions of physicians to the standards of care expected of them under the law, drawing on the abandonment by states over time of rules holding physicians to standards determined by local customs and the contemporaneous adoption of national-standard rules. Using data on broad rates of surgical interventions at the county-by-year level from the Area Resource File, we find that local surgery rates converge towards national surgery rates upon the adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…These findings complement our prior research (Frakes, Frank and Seabury 2015), where we found that treatment utilization patterns are sensitive to the adoption of national-standard rules.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…These findings complement our prior research (Frakes, Frank and Seabury 2015), where we found that treatment utilization patterns are sensitive to the adoption of national-standard rules.…”
supporting
confidence: 90%
“…Collectively, the findings from the present paper and from Frakes, Frank and Seabury (2015) and Frakes (2013) raise a question regarding the mechanisms underlying the treatment intensity responses documented in these prior works. Was the convergence in practices documented in these studies likely attributable to given physicians modifying their practices in connection with altered clinical expectations-e.g., do given physicians practice more intensively when an initially low-intensity regions adopts a national standard rule that expects physicians to follow more intensive styles?…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Other studies have found that requiring physicians to follow national standards as opposed to local standards leads to standardization of clinical practices. 56,57 Recent approaches to liability reform aim to discourage defensive medicine while fostering process improvement both at the physician and at the system level. 'Alternative dispute resolu- also proposed reform ideas such as safe harbors for providers who adhere to clinical practice guidelines, a version of administrative 'health courts' and protection of apologies from use in malpractice litigation.…”
Section: Discussionmentioning
confidence: 99%